STUDI KETIMPANGAN DISTRIBUSI PENDAPATAN DAN PERBANDINGAN KLASIFIKASI WILAYAH KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT TAHUN 2010-2013 - B01109082, V. Inggi Setiawan (Jurnal Pembangunan dan Pemerataan, 2016)
This study aims to to classify areas with matrix typologies klassen that divides 14 districts/city into 4 quadrant consisting of the area forward, regional forward but depressed, developing areas and the regions left. After saw the gap the income distribution of districts/city income capita above and under the average West Kalimantan. In this research the analysis used is descriptive analysis qualitative thus research this explains variables related in classifying areas according to typologies klassen in West Kalimantan. To analyze lameness happened, methods used is for ratio. During the period 2010-2013, some districts/city in West Kalimantan diverted typologies areas. But from the analysis also found that a number of districts/city never diverted quadrant or static. But district/city static is at quadrant I are singakawang city and melawi district. District/city static is at quadrant are Kuburaya District II. District/city static at III quadrant are Bengkayang District and Pontianak District. On quadrant IV in the period of 2010-2013 no district/city static this is at quadrant. From 14 districts/city, there are five districts/city per capita income above average West Kalimantan during the period 2010-2013. Of these districts are is Ketapang, Sintang, Melawi, Pontianak City and Singkawang City. Lameness happened to districts/city not show the condition lameness special. There were 9 districts per capita income below the average West Kalimantan. From 9 districts that is, 6 districts such as level lameness continue to increase until 2013. Over a period of 2010-2013 more than 50 percent of districts as the areas that had been left behind in West Kalimantan. An area that had been left behind this cannot be separated from lack of investment and development in the area. The number of disparities West Kalimantan still are categorized was since on average lameness happened in west kalimantan 're either 0,30-0,49 figures. Keywords: Economic Growth, Per Capita Income, Inequality Of Income Distribution, Gini Ratio, Typology Klasen, West Kalimantan.